Интерсемиотический и прагмасемантический анализ цикла мемов „Дворец для Путина” - Żanna Sładkiewicz (Studia Rossica Posnaniensia)
The article is devoted to the analysis of the pragmatics and semiotics in the productive comic genre of digital communication – the political meme. The empirical material consists of actual internet heterogeneous texts, created after the publication of Alexei Navalny’s film “Palace for Putin”. The comic content is viewed as a way of defusing the public tension of the sanctioned protest, an instrument for interpreting and discussing current social reality, as well as a method of demonizing a political subject “them”. The research assumes multimodality of the media environment and its products. It considers verbal, iconic and metagraphic ways of realizing the pragmatic intentions of the participants in the communication process. The author examines the initial situation (proto situation) that caused a communicative reaction of the internet users in the form of memes, analyzes the essence of a political meme as a heterogeneous text. The article describes the structural organization of memes, the syntactic and semantic relations of the verbal and iconic parts, as well as the use of intertextuality to concisely and expressively transmit new meanings.